EVALUASI KEBIJAKAN RETRIBUSI PERIZINAN TERTENTU (Studi Izin Trayek Di Kecamatan Ujung Batu Kabupaten Rokan Hulu) - Safores, Defkendri Novaldi; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the cause of the levy is not optimal route permits the implementation of policies in the District of Rokan Hulu Ujung Batu area of sector revenue realization retribution route permits have not met the targets set by the local government. The unmet realization of the reception area of the sector route permits that one of them caused by the mode of licensing services that have not been touched up at the district level. This study rests on a theoretical analysis of policy evaluation and was conducted using qualitative and descriptive data analysis.This study shows that the levy collection process route permits in accordance with procedures established by the Government of Rokan Hulu. That associated with not achieving the target reception area of the sector route permit retribution caused by a number of vehicles that do not have route permits and does not extend the route permits possessed. Not achieving the revenue target area of the route permit retribution sector caused by disobedience entrepreneurs in arranging transport route permits of both new and extension of route permits. Meanwhile, community groups tend to be passive for the licensing of public transportation that they used. Have a both internal and external obstacles that cause employers are reluctant to take care of transport route permits.Keywords: Policy, Route Permits , Evaluation